ASSESSING THE SIGNIFICANCE OF RESERVATION SYSTEMS IN HOTELS OF DELHI: A COMPARATIVE ANALYSIS OF HOTEL’S OWN AND THIRD-PARTY PLATFORMS (CAHIERS MAGELLANES-NS, 2024)
Reservation system is a software application utilized in the hotel sector to efficiently oversee room availability, pricing, and reservations. This study examines the significance of reservation systems in hotels located in Delhi, India, with a focus on both hotel-owned and third-party platforms. The objective is to assess the effectiveness of these systems in various dimensions of guest satisfaction and operational efficiency. A one-sample t-test analysis, utilizing IBM SPSS software version 26, was conducted to evaluate five key factors: Technological Innovation and Guest Engagement, Guest Satisfaction and Loyalty Enhancement, Efficient and Reliable Reservation Management, Comprehensive Customer Experience Enhancement, and Flexible Booking and Refund Policy. Through sample size of 110 front desk managers from 32 Ministry of Tourism-approved hotels participated in the study, providing insights into the performance of hotel websites and third-party reservation systems (OTAs) Online travel agencies. Data collection employed a convenience sampling method, targeting guests from Ministry of Tourism-approved 4-star, 5-star, and 5-star deluxe hotels in Delhi. Study revealed significant findings across most factors, highlighting the importance of reservation systems in enhancing guest experiences and hotel operations. However, specific variables within hotel-owned and third-party platforms were found to be non-significant, suggesting areas for potential improvement or reconsideration. For hotel-own reservation systems, variables related to guest engagement, navigation facilities, cancellation policies, and multilingual options were identified as non-significant. Similarly, certain variables within third-party reservation systems, such as HD visual effects, special packages for repeat guests, guest grievance handling, and multilingual options, were deemed non-significant. Overall, the study underscores the critical role of reservation systems in driving guest satisfaction, loyalty, and operational efficiency within the hotel industry. By identifying significant factors and areas for improvement, hoteliers can optimize their reservation systems to meet guest expectations and maintain competitiveness in the market.